(untitled) (Research, Society and Development, 2022)
Cancer is a disease that presents as its main characteristic the uncontrolled growth of cells, which is currently numerous people annually. The available treatments such as chemotherapy cause many adverse effects in cancer patients because it also reaches the viable cells of the body. Plants have a wide variety of pharmacologically active compounds and are major sources for the development of new drugs with oncological potential. Biodiversity has been prospected in recent decades to discover and develop new drugs that are safer and more effective in the battle against cancer, acting more selectively with fewer toxic effects. Some drugs currently used in cancer treatment are derived from plants. Therefore, the present review aimed to address the general aspects of cancer and the pharmacological potential of secondary metabolites in cancer treatment. Through the bibliographic survey, it is concluded that there is much to be explored and plants present numerous therapeutic possibilities.